Displaced center of pressure on the treated side in individuals with essential tremor after radiofrequency ablation: a longitudinal case–control study - Sato, Atsuya; Taira, Takaomi; Kitada, Kazuya; Ando, Toshiki; Hamaguchi, Toyohiro; Konno, Michiko; Kitabatake, Yoshinori; Ishioka, Toshiyuki (Frontiers in Neurology, 2023)
Background: Essential tremor (ET) is a common involuntary movement disorder (IMD). Radiofrequency ablation (RFA) targeting the ventral intermediate nucleus (Vim) of thalamus is a stereotactic neurosurgery performed in individuals with ET when pharmacotherapy is no longer effective. Though the reasons remain largely unclear, certain adverse events are known to appear post-RFA. These may be due to functional changes in the Vim, related to RFA-induced tremor reduction, or an adverse reaction to compensatory movement patterns used to perform movements in the presence of tremor symptoms. Objective: This study aimed to understand the characteristics of post-RFA symptoms in individuals with ET. Methods: In a longitudinal case-control study, we compared post-RFA symptoms between individuals with ET who underwent Vim-targeted RFA and those with IMD who underwent non-Vim-targeted RFA. Symptoms were compared preoperatively, and 1-week and 1-month postoperatively. Quantitative assessments included center-of-pressure (COP) parameters, grip strength, Mini-Mental State Examination, two verbal fluency tests, and three types of physical performance assessments (upper extremity ability, balance ability, and gait ability). Results: Individuals with ET after RFA showed horizontal displacements of the COP to the treated side (the dominant side of the RFA target's hemisphere) at 1-week postoperatively, compared to the preoperative period. The horizontal COP displacement was associated with balance dysfunction related to postural stability post-RFA. Other COP parameters did not significantly differ between the ET and IMD groups. Conclusions: The COP displacement to the treated side may be due to a time-lag in adjusting postural holding strategies to the long-standing lateral difference in tremor symptoms associated with tremor improvement after RFA.